Concrete and culture : a material history - Forty, Adrian, 1948- (Reaktion, 2012)
"Breaks new ground by charting concrete's effects on culture since its reinvention in the modern period, examining the ways it has changed our understanding of nature, of time and of materiality. This book discusses architects' responses to and uses of concrete while also taking into account the role it has played in politics, literature, cinema and labour relations, as well as in present-day arguments about sustainability."--Jacket